(untitled) (Research, Society and Development, 2021)
This article aims to discuss or conceive the quilombo in a historical and theoretical perspective through a literature review on or subject. As an object of investigation, the delimitation of the quilombola community council is linked since its origin in the African territory, its insertion in the Brazilian reality and, in this sense, with a non-state approach to Ceará and, more specifically, to the region. do Cariri Cearense, aimed at a specific quilombola community, or Sítio Arruda. We note that in its African constitution, or quilombo, it is a revolutionary social institution. However, the quilombos in Brazil were distancing themselves from the African model, building their own costumes. The concept of quilombo became synonymous with black people and should be understood as a framework for resistance and organization. From the 1970s onwards, two black social movements also developed or strengthened. This phenomenon, caused by changes arising from the 1988 Constitution, will be the result or restoration of the territory or territory of black communities. In the State of Ceará, a false idea of ​​the absence of two blacks persisted. However, during the 1980s, a process of “discovery” of black groups began, evidencing the quilombola presence and not the State and the constitution of the black movement. Finally, from the constitution of the identity of the quilombola community of Sítio Arruda, we see that migration to the Cariri region of Ceará should be considered an important factor in the formation and consolidation of the local quilombola context.